Yes, substitute a=2.
14 - 4 + 6 - 6 = -2
8 - 10 = -2
Answer:
a = 1
b = -3
c = -2
Step-by-step explanation:
Answer:
-4
Step-by-step explanation:
First, multiply
-12*2+8*2/-5-(-7)
= -8/-5-(-7)
Second do -5-(-7)
= -8/2
= -4
Answer:
-7 × (-4) will have a positive product.
Step-by-step explanation:
product of the two number are positive only if the two numbers have the same sign either both (+) or both (-).
and -7 × (-4) = 28.
here 28 is positive.
The equation for a hyperbola is (x-h)/a - (y-k)/b = 1
Or (y-k)/a - (x-h)/b = 1
h represents the x value of the coordinate
k value represents the y value of the coordinate
together they represent a point, which is the center
So (h,k) is (x,y)
The asymptote is y-k = +/- b/a (x-h)
The transverse is the line that goes through the hyperbola.